Erratum: Naruse, T., Chan, T.-Y., Tan H.H., Ahyong, S.T. & Reimer, J.D. (2012) Scientific Results of the Marine Biodiversity Expedition—KUMEJIMA 2009. Zootaxa, 3367, 1–280. - Naruse, T.; Chan, T. Y.; Tan, H. H.; Ahyong, S. T.; Reimer, J. D. (Zootaxa, 2012)
(Erratum)